(untitled) (Innovative professional education, 2022)
The introduction of test control in the educational process of the institution of professional preliminary higher education allows to implement an individually oriented approach in assessing the level of knowledge, which increases the quality of training of future specialists - masters of industrial training. Test control increases the level of the educational process, promotes the independent work of students, gives the teacher the opportunity to check a significant volume of work and analyze students’ mastery of the studied material